OP01 Volunteer-led advance care planning advisory and education services: an evaluation of a new model for australian service delivery. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Kelly, H; Nolte, L; Verde, A; Detering, K
Abstract : Background: Research on utilising volunteers in advance care planning (ACP) is limited. Advance Care Planning Australia delivers initiatives to increase awareness and uptake of ACP among Australians. This study aimed to evaluate the reach and satisfaction with two unique volunteer-led ACP initiatives: a national advisory service and a community education program. Methods: Volunteers were trained and mentored. Standard operating procedures and presentations guided service delivery, resulting in clearly documented program resources that can be used by other groups. Services were provided to consumers and health professionals. Follow-up measures included satisfaction with the advisory service and awareness, knowledge and confidence regarding ACP and the education program. Results: During 1 January to 30 September 2018, the national advisory service received 1284 enquiries; 572 from health professionals, 712 from consumers. Fifty percent of calls were responded to by volunteers and 50% by health professionals. Sixty-two enquirers completed an evaluation survey, with 87% of those indicating that they were satisfied or extremely satisfied with the service. During 30 May to 18 September 2018, volunteers delivered 15 presentations to 247 people. Of those, 149 attendees completed an evaluation survey. Prior to the session, 27% had never heard of ACP whereas 42% had. Post session, 76% of respondents indicated confidence to have ACP conversations with family and friends, 65% indicated confidence to talk to their healthcare professionals. Conclusion: Volunteer-led models of service delivery can help meet organisational outcomes. Volunteers can deliver high rates of satisfaction and increase community confidence in having advance care planning conversations.